2022
DOI: 10.4025/actascibiolsci.v44i1.59739
|View full text |Cite
|
Sign up to set email alerts
|

An analytical method for the quantitative determination of iron ion chelating capacity: development and validation

Abstract: Iron is a fundamental microelement for human life; however, deficiencies or excesses of these metal ions can cause severe complications and mortality. Chelators are compounds that bind and inhibit iron. Ultraviolet-visible (UV-vis) spectrophotometric methods are key analytical tools in the identification of chemical entities, with the benefits of having good precision and accuracy, and the equipment being easily available as well as quick and simple to implement. In this study, we aimed to provide an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
4
1
0
Order By: Relevance
“…These results were consistent with those reported by Harke et al 28 who found 78–88% repeatability in results during Fe +3 detection in food samples using biogenic silver nanoparticles. A similarity index was observed between the current findings and those of da Silva Santos et al, 31 where <5 RSD % in intraday results was obtained during quantification of Fe ion chelating capacity using a newly developed analytical method.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…These results were consistent with those reported by Harke et al 28 who found 78–88% repeatability in results during Fe +3 detection in food samples using biogenic silver nanoparticles. A similarity index was observed between the current findings and those of da Silva Santos et al, 31 where <5 RSD % in intraday results was obtained during quantification of Fe ion chelating capacity using a newly developed analytical method.…”
Section: Resultssupporting
confidence: 87%
“…Values for relative standard deviation (%) are displayed in Table 3 . The percent recovery of 100.8, 103, and 104 for each level showed a close resemblance with the recoveries (%) stated by da Silva Santos et al 31 obtained at three concentrations (6.2, 50, and 200 μg/mL) during analytical method validation of iron ion chelating quantification with EDTA. Inter-person precision results were agreed with the findings of da Silva Santos et al, 31 who reported ruggedness RSD value at <5% during his research work on method validation of iron ion estimation.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…47,48 We minimized the background signal by incorporating ethylenediaminetetraacetic acid (EDTA) in the ferrozine side of the sample distribution layer. 49,50 We tested both the effect of different EDTA and ferrozine concentrations on the signal to background ratio (Tables S5 and S6 †). As the concentration of ferrozine increased, the intensities of both the signal formed at the readout zone and the background increased.…”
Section: Iron (Fe(iii))mentioning
confidence: 99%